Rejection and Disaffiliation in Twenty-First Century American Immigration Narratives - Daily, Katie (Pivotal Studies in the Global American Literary Imagination, 2018)
Rejection and Disaffiliation in Twenty-First Century American Immigration Narratives examines changing attitudes about national sovereignty and affiliation. Katie Daily delinks twenty-first century American immigration narratives from 9/11, examining genre alterations within a scope of literary analysis that is wider than what "post-9/11" allows. What emerges is an understanding of the speed at which the rhetoric and aims of many twenty-first century immigration narratives significantly depart from the traditions established post-1900. Daily investigates a recent trend in which novelists and filmmakers question what it means to be an immigrant in contemporary America and explores how these "disaffiliation" narratives challenge some of the most fundamental traditions in American literature and society.